Bottom-Up Synthesis of Necklace-Like Graphene Nanoribbons - Schwab, Matthias Georg; Narita, Akimitsu; Osella, Silvio; Hu, Yunbin; Maghsoumi, Ali; Mavrinsky, Alexey; Pisula, Wojciech; Castiglioni, Chiara; Tommasini, Matteo; Beljonne, David; Feng, Xinliang; Muellen, Klaus (Chemistry - An Asian Journal, 2015)
Graphene nanoribbons (GNRs) with an unprecedented "necklace-like" structure were synthesized through a bottom-up chemical approach, based on the oxidative cyclodehydrogenation of tailor-made polyphenylene precursors. A polycyclic aromatic hydrocarbon consisting of 84 sp2 carbons (C84) was also synthesized and characterized as a model compound. Characterizations by a combination of MALDI-TOF MS and FTIR, Raman, and UV/Vis absorption spectroscopy validated the formation of the necklace-like GNRs. The absorption spectrum and DFT calculations revealed a bandgap of approximately 1.4eV for this novel GNR system, which has not been attained with other GNR structures, enabling further fine-tuning of GNR bandgaps by structural modulation.
CRIS-Team Scopus Importer:2023-03-20
Keywords: dehydrogenation; graphene; nanostructures; polycycles; vibrational spectroscopy